Comparison of the effects of chlormadinone acetate versus drospirenone containing oral contraceptives on metabolic and hormonal parameters in women with PCOS for a period of two-year follow-up - YILDIZHAN, BEGÜM; ANIK İLHAN, GÖKÇE (TAYLOR & FRANCIS LTD, 2015)
Objective: A randomized trial to compare the effects of two oral contraceptive pills containing either chlormadinone acetate or drospirenone as the progestogen, in women with PCOS for a period of two-year follow-up. Methods: Group A received ethinyl-estradiol 0.03 mg + drospirenone 3 mg (EE+DRSP; n=56) and Group B received ethinyl-estradiol 0.03 mg + chlormadinone acetate 2 mg (EE+CMA; n=50). Clinical, hormonal and biochemical parameters were compared at baseline, 6 months, 12 months and 24 months. Results: The increase in total cholesterol and hsCRP levels was statistically significantly higher at 6, 12 and 24 months in Group B when compared with Group A. The change in the high-density lipoprotein cholesterol level at the 24 months of treatment was statistically significantly higher in Group A. Group A has a significantly higher reduction in FAI at 6 and 24 months, in FGS at 6, 12 and 24 months and in HOMA-IR index at 12 and 24 months when compared with Group B. Conclusions: Drospirenone containing combined oral contraceptive (COC) is found to have more favorable effects on lipid profiles, hsCRP levels, insulin resistance and hyperandrogenism when compared with the CMA containing COC and appears to be more beneficial for the long-term cardiovascular and metabolic aspects of PCOS.
Keywords: Hirsutism; hormonal contraception; insulin resistance; ovary; polycystic ovary syndrome; POLYCYSTIC-OVARY-SYNDROME; INSULIN-RESISTANCE; CARDIOVASCULAR RISK; CYPROTERONE-ACETATE; 3 MG; MU-G; METFORMIN; ALDOSTERONE